Self-assembly of l-cysteine–gold nanoparticles as chiral probes for visual recognition of 3, 4-dihydroxyphenylalanine enantiomers1. Issue 34 (15th April 2015) - Zhang, Lin; Xu, Chunli; Song, Guoxin; Li, Baoxin
<x xml:space="preserve">Abstract</x> A simple protocol to distinguish enantiomers is extremely intriguing and useful.